An Act for better settling and regulating the Militia of this Colony of New-Jersey, for the repelling Invasions, and Suppressing Insurrections and Rebellions. Passed May 8, 1746. Section 3. Officers and Soldiers to behave well while under Arms; and, Section 23. - (:unkn) unknown (General Publisher, 1746)
Prohibited the sale of any strong liquor to members of the militia. Violators fined three pounds.
--
Keywords: ARMED FORCES